Using Youtube to Improve Students' Writing Ability - Sitti Hardianti; Amelfi Saosang (BABASAL English Education Journal, 2022)
This study aims to determine the improvement of students' ability in writing descriptive text using YouTube media. The research was conducted from August to September 2021 on first-grade students of SMAN 3 Bunta. This research is quantitative research with 29 students of class X MIA SMAN 3 Bunta as research subjects. In searching for research data, a written test was used which contained pre-test and post-test. The instrument is given to find out how far the students' writing ability is before and before the test. The results showed that the t-count was 5.825. Therefore, the t-table with a one-tailed significance value is 0.05, and it is found that the t-table is 1.701. This shows that the t-count is higher than the t-table. In other words, there was a significant improvement in students' writing ability after using YouTube. Therefore, this research hypothesis can be accepted. The mean pre-test score was 53.17 and the mean post-test was 68.31. This means that the average score of students is increased by 15.14. Thus, the results of the study conclude that using YouTube can improve students' ability in writing descriptive text at SMAN 3 Bunta.